THU0023 Complex immunophenotyping stratifies patients with primary sjÖgren's syndrome, systemic lupus erythematosus and secondary sjÖgren's syndrome associated with systemic lupus erythematosus into distinct clinically relevant groups with potential therapeutic implications. (12th June 2018) - Thompson, N.; Gandhi, A.; Radmmore, R.; Gupta, V.; Robinson, G.; Martin-Gutierrez, L.; Isenberg, D.; Jury, E.; Ciurtin, C.
Abstract : Background: Similarities in the clinical and laboratory features of patients with primary Sjögren's syndrome (pSS) and systemic lupus erythematosus (SLE) have led to attempts to treat pSS and SLE patients with similar biologic therapeutics. However, the results of many clinical trials are disappointing and no effective treatments are available for pSS and few for SLE patients with refractory disease. Objectives: To identify novel patient endotypes using in depth immune phenotyping that facilitates the selection of biological therapies for patients regardless of diagnostic labels. Methods: Peripheral blood was collected from patients with pSS (n=55), SLE (n=38), SS/SLE (n=15) and age/sex-matched healthy controls (HCs) (n=34). In-depth phenotyping of peripheral B and T-cell subsets by flow-cytometry, followed by unsupervised cluster analysis were performed. ROC analysis identified immune signatures characteristic for every cluster (endotype). Results: Patients with pSS, SLE and SS/SLE had both unique and shared defects in immune cell phenotype. Hierarchical clustering of CD19 + B-cells, CD4 + and CD8 + T-cells across the three disease groups identified five distinct endotypes spanning diagnostic boundaries. Three of the endotypes had distinct immune signatures, characterised by predominantly B-cell, T-cell memory or CD4 + /CD8 + T-cell subset fingerprints respectively, while two clusters had no distinct immune profiles. Notably, clinical and disease features were not significantly different between clusters. Conclusions: The results demonstrated that immune cell biomarkers could be used to re-classify patients in a manner that reflects their underlying immunopathogenesis. Characterisation of a patient's endotype could lead to better stratification of patients for selection of therapeutic targets in clinical trials. References: [1] Nocturne, G. & Mariette, X. Advances in understanding the pathogenesis of primary Sjogren's syndrome. Nat Rev Rheumatol2013;9:544–556. [2] Sada, P.R., Isenberg, D. & Ciurtin, C. Biologic treatment in Sjogren's syndrome. Rheumatology (Oxford)2015;54:219–230. Disclosure of Interest: None declared